2023
DOI: 10.3390/jcm12093092
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Value of the Sentinel Lymph Node Technique in Patients with Muscle-Invasive Bladder Cancer

Abstract: Background: The optimal limits of the bilateral pelvic lymph node dissection (PLND) template in bladder cancer treatment remain controversial. This study aimed to investigate whether radio-guided sentinel node (SLN) detection is a reliable technique for the perioperative localisation of potential lymphatic metastasis during cystectomy for muscle-invasive bladder cancer (MIBC). Materials and Methods: We studied 54 patients with pT2-pT4 MIBC who underwent cystectomy with extended PLND (ePLND) augmented by the SL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…In the transurethral group, two patients did not show LN visualization intraoperatively because of inadequate control of parameters such as injection depth and intravesical pressure. Other studies have also confirmed that SLN mapping should be considered a supplementary approach to PLND during RC, rather than as a replacement of routine bilateral PLND ( 17 ).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In the transurethral group, two patients did not show LN visualization intraoperatively because of inadequate control of parameters such as injection depth and intravesical pressure. Other studies have also confirmed that SLN mapping should be considered a supplementary approach to PLND during RC, rather than as a replacement of routine bilateral PLND ( 17 ).…”
Section: Discussionmentioning
confidence: 94%
“…ICG-guided SLN detection has been successfully applied in clinical practice for the diagnosis of breast cancer ( 13 ), penile cancer ( 14 ), and melanoma ( 15 ). However, the complexity of bilateral lymphatic drainage in the bladder leads to a high false-negative rate and low detection rate, which limits the application of ICG in bladder cancer SLNB ( 16 , 17 ).…”
Section: Introductionmentioning
confidence: 99%